70.8k views
1 vote
-40-2(3m+1/2)=7m-2 what does m equal

User Sharrone
by
6.4k points

1 Answer

4 votes

Answer:
m = −3

Explanation:

Hey there! I will give the following steps, if you have any questions feel free to ask me in the comments below.

Step 1: Expand.

−40 − 6
m − 1 = 7
m − 2

Step 2: Simplify −40 − 6
m − 1 to −6
m − 41.

−6
m − 41 = 7
m − 2

Step 3: Add 6
m to both sides.

−41 = 7
m − 2 + 6
m

Step 4: Simplify 7
m − 2 + 6
m to 13
m − 2.

−41 = 13
m − 2

Step 5: Add 2 to both sides

−41 + 2 = 13
m

Step 6: Simplify −41 + 2 to −39.

−39 = 13
m

Step 7: Divide both sides by 13.


(39)/(13) =
m

Step 8: Simplify
(39)/(13) to 3.

−3 = m

Step 9: Switch sides.


m = −3

~I hope I helped you! :)~

User Tani
by
5.9k points